Is the learning organisation still alive?. Issue 2 (6th February 2017) - Pedler, Mike; Burgoyne, John G.
Abstract : Purpose: It has recently been suggested that the learning organisation (LO) is dead (Pedler, 2013). The authors make the case here that it is still alive. This paper provides a brief history of LO and organisational learning, follows this with some survey findings, a discussion and an exploration of some related contemporary issues and concludes with an overview and summary of the conclusions. Design/methodology/approach: Survey of practitioners. Findings: From this small survey, whilst some of the 16 respondents are still excited by the idea, a larger group sees the learning organisation as more of a background concept, performed in ways that might not fit with the aspirations of 20 years ago. Research limitations/implications: The authors started with the question: is the LO idea still alive in 2016? No clear answer emerges. Given the variety of the responses, it is difficult to sum them up in a simple way. The yea-sayer will find plenty of evidence for the LO's continued existence and relevance, but the nay-sayers will also feel at least partly vindicated. What does emerge clearly arise from the mixed messages, are the opportunities for further research. Practical implications: This paper calls for further research and suggests useful directions. Social implications: LO is still seen as socially useful. Originality/value: The paper is based on small empirical sample of practitioners who display multivocality on this concept.